PENGARUH VARIASI KONSENTRASI KATALIS ASAM SULFAT PEKAT TERHADAP HASIL DERAJAT ESTERIFIKASI ETIL LAURAT - Jessica Margareta Jaya; Maria Mita Susanti (Jurnal Ilmiah Medsains, 2020)
Ethyl laurate can be synthesized through an esterification process by reacting lauric acid and ethanol plus H2SO4(p) as a catalyst. The esterification reaction requires a catalyst to accelerate the reaction besides the influence of the addition of the catalyst concentration also affects the ester results so it is necessary to do research that aims to determine the effect of catalyst H2SO4(p) concentration on the results of ethyl lauric esterification. This type of research is an experimental study to determine the effect of variations in H2SO4 catalyst concentration on the synthesis results of ethyl laurate. The experimental design used in this study was a factorial Completely Randomized Design (CRD), which was a comparison of the variation in catalyst H2SO4(p) concentration. The variables observed were variations in H2SO4 (1%, 2%, 3%, 4% and 5%) catalyst concentrations on the esterification degree reacted for 5 hours with a comparison of the variation of the molar ratio of lauric acid and ethanol used 1: 7. Analysis of statistical data obtained was tested using the Oneway Anova test. The results showed that variations in H2SO4(p) catalyst concentration had an effect on the results of the esterification degree. The best degree of esterification was obtained at concentration catalyst H2SO4(p) 4%, which amounted to 90.24%. Statistical data analysis obtained a significant value of 0,000 (p <0.05) which means that there is an influence of variations in the catalyst concentration on the synthesis results of ethyl laurate.